Mating alters the link between movement activity and pattern in the red flour beetle. (28th April 2017) - Wexler, Yonatan; Wertheimer, Keren‐Or; Subach, Aziz; Pruitt, Jonathan N.; Scharf, Inon
Abstract: Mating in arthropods is costly and has negative effects on survival. Such effects are often more strongly expressed when individuals are simultaneously exposed to other stress sources. Consequently, the behaviour of virgin and mated individuals often differs. Mated females, for example, search for suitable oviposition sites, whereas virgin females search more for mates. In the present study, we examine the effect of mating separately for females and males on four key behaviours of the red flour beetles: movement activity, movement along the edges of an arena, latency to emerge from shelter and preference for dark microhabitat. After mating, both sexes increase their activity at the same time as moving less along the arena edge, leading to a change in movement pattern. Females possibly change their movement pattern to locate suitable oviposition sites, whereas males perhaps do so to detect additional females with which to mate. Latency to emerge from shelter and dark preference are not influenced by mating, although they increase when measured again after 1 week. Of these behaviours, only movement activity is consistent at the individual level. We also examine whether mating incurs a cost as expressed in the time required to recover from a chill‐coma. The latter is a common proxy of cold tolerance in ectotherms. By contrast to our prediction, mating has no effect on chill‐coma recovery time, suggesting that either a single mating event does not incur sufficient stress or that there is possibly no trade‐off between the energetic cost of mating and of cold tolerance.